SPARC Levels Modulate the Capacity of Mitomycin to Inhibit the Proliferation of Human Tenon’s Capsule Fibroblasts - Yuanyuan Guo; Shouxiang Ni; Weiyan Zhou; Jiangping Hou; Jiaquan Shen (Journal of Ophthalmology)
Purpose. To evaluate the role of SPARC in the antiproliferation effect of MMC on human Tenon’s fibroblasts (HTF). Method. Sixteen PACG patients aged 59 ± 10 years (31–72 years), including 6 males and 10 females, were recruited. Tenon tissue was harvested during filtering surgery. Cell density was evaluated after MMC application with different concentrations and application times, by which the optimized MMC application modality was determined. MMC, si-SPARC, or SPARC protein was used when needed to evaluate the cell densities under different conditions, by which the role of SPARC in MMC-mediated antifibrotic process was identified. Results. Considering that the cell densities, as well as SPARC expression on mRNA and protein levels, are relatively stable when the MMC concentration is higher than 0.02% and exposure time longer than 90 s, we chose the MMC application pattern with 0.02% and 90 s as an optimized pattern for the downstream work. Compared to control, the si-SPARC and MMC downregulated the SPARC protein by 91% (P<0.01) and 65% (P<0.01) and mRNA by 96% (P<0.01) and 64% (P<0.01), respectively. MMC decreases the cell densities by 53.50% compared to control. si-SPARC + MMC dramatically deceased the cell density no matter compared to the control group (P<0.01) or MMC group (P<0.01); correspondingly, the relative collagen gel area in the MMC + si-SPARC group was higher than that in the MMC group or si-SPARC group (P<0.05). The reactive oxygen species expression in the MMC + si-SPARC group is higher than that in the MMC group (P<0.05). Conclusion. This study demonstrates that in HTF, (1) MMC downregulates the expression of SPARC in protein and mRNA levels; (2) SPARC depletion has synergistic effect on the antifibrotic effect of MMC; and (3) reactive oxygen species are the possible mediator in the antifibrotic effect of MMC and si-SPARC.